Differentiating existing habitat of the invasive tamarisk (Tamarix spp.) from potential habitat of the endangered Southwestern Willow Flycatcher (Empidonax traillii extimus) through maximum entropy modeling - York, Patricia M., author; Stohlgren, Thomas J., advisor; Graham, James J., committee member; Flather, Curtis H., committee member; Sloane, Sarah, committee member (Colorado State University. Libraries, 2010)
Biological control of the exotic plants known collectively as tamarisk (Tamarix spp, saltcedar, tamarisk) in southwestern states is controversial regarding the protection of the federally endangered Southwestern Willow Flycatcher (Empidonax traillii extimus). The songbird sometimes nests in tamarisk where floodplain-level invasion replaces native habitat. Biological control with the saltcedar leaf beetle (Diorhabda elongate) began along the Virgin River, Utah, in 2006, enhancing the need for comprehensive understanding of the tamarisk-Flycatcher relationship. I used maximum entropy (Maxent) modeling to separately quantify the current extent of dense tamarisk habitat (>50% cover) and the potential extent of habitat available for E. traillii extimus within the studied watersheds. I used transformations of 2008 Landsat Thematic Mapper images and a digital elevation model as environmental input variables. Maxent models performed well for the Flycatcher and tamarisk with Area Under the ROC Curve (AUC) values of 0.960 and 0.982, respectively. Classification of thresholds and comparison of the two Maxent outputs indicated little spatial overlap between predicted suitable habitat for E. traillii extimus and predicted dense Tamarisk stands. Dense tamarisk habitat comprised 1,000 km2 within the study area, of which 8.5% was also modeled as potential habitat for E. traillii extimus. Potential habitat modeled for the Flycatcher constituted 230 km2, of which 38.1% also contained dense tamarisk habitat. Results showed that both native vegetation and dense tamarisk habitats exist in the study area and that most tamarisk infestations do not contain characteristics that satisfy the habitat requirements of E. traillii extimus. Based on this study, effective biological control of Tamarix spp. may initially reduce the suitable habitat available to E. traillii extimus within the study area, but has the potential to increase suitable habitat if native vegetation replaces tamarisk in biocontrol areas.
Department Head: N. LeRoy Poff.